Factors Influencing Profit Efficiency of Banking in Indonesia - Kadang, Juliana; Djoko Mursinto; Rudi Purwono (Universitas Airlangga, 2018)
This study intends to test, analyze, and verify the influence of bank size, capital adequacy, liquidity, credit risk, and market power on commercial banks profitability. Quantitative research methods applied in this study are explanatory method, which aims to analyze the influence of independent variables on dependent variable and descriptive method to describe the object studied. The study also applies Stochastic Frontier Analysis (SFA) approach to estimate the technical efficiency of commercial banks. The results show that bank size, capital adequacy (CAR), liquidity (LDR), credit risk (NPL) and market power significantly affect the profitability of commercial banks in Indonesia in the period of 2010-2016. The result of yearly financial report of each bank is caused by the fact that: 1). some banks are in the process of mergers; 2). the allowance for impairment losses on financial assets and non-financial assets increased primarily with banks in the merger process; 3). banks have credits in default status and under special surveillance with an increasing amount of credits from year to year. Keywords: Profit Efficiency, Bank Size, Capital Adequacy, Liquidity, Credit Risk, and Market Power. JEL Classification: G21, E22, G32, L11